Perpetrators Of Violence Against Elementary School-Aged Children In Families In The Koto Tangah Padang City, Indonesia - Meri Neherta; Lili Fajria; Arif Rohman Mansur; Aisyah Rahmadini (Universitas Aisyah Pringsewu, 2023)
Violence against children in the family that is perpetrated by those closest to and well-known to the child is an iceberg phenomenon. Violence experienced by children has physical and psychological impacts that will interfere with their growth and development. This study aims to find out who is the perpetrator of violence against elementary school-age children in the family. The descriptive research design was carried out in the city of Padang in October 2022 – December 2022. The research sample was 1000 elementary school-age children, taken using the simple random sampling. Using a standardized questionnaire from the Child Abuse Screening Tool Questionnaire (ICAST-C) to measure violence against children. Presentation of data using a frequency distribution. The results showed (95.10%) psychological violence, (94.60%) physical violence, (31.60%) social violence, and (22.10%) sexual violence. Most perpetrators were mothers (80%), fathers (61.3%), grandfathers (14.8%), brothers (15.4%), and uncles (13.1%). Conclusions: (95.10%) elementary school-age children have experienced violence in the family, where the perpetrators are mothers, fathers, grandfathers, brothers, and uncles. It is recommended that all prospective brides and grooms receive health education about the basic needs of child development and the role and function of the family in creating a prosperous family. Abstrak: Kekerasan terhadap anak dalam keluarga yang dilakukan oleh orang terdekat dan dikenal baik oleh anak, merupakan fenomena gunung es. Kekerasan yang dialami anak berdampak pada fisik dan psikis yang akan mengganggu pada pertumbuhan dan perkembangannya. Penelitian ini bertujuan untuk mengetahui siapakah pelaku kekerasan terhadap anak usia sekolah dasar dalam keluarga. Rancangan penelitian deskriptif dilaksanakan di Kota Padang pada bulan Oktober 2022 – Desember 2022. Sampel penelitian adalah 1000 anak usia sekolah dasar, diambil dengan menggunakan simple random sampling. Memakai kuesioner baku dari Child Abuse Screening Tool Questionnaire (ICAST-C) untuk mengukur kekerasan terhadap anak. Penyajian data menggunakan distribusi frekuensi. Hasil penelitian menunjukkan (95,10%) anak telah mendapatkan kekerasan psikis, (94,60%) kekerasan fisik, (31,60%) kekerasan sosial, dan (22,10%) kekerasan seksual. Pelaku terbanyak adalah ibu (80%), ayah (61,3%), kakek (14,8%), saudara laki-laki (15,4%), dan paman (13,1%). Kesimpulan: (95,10%) anak usia sekolah dasar pernah mengalami kekerasan dalam keluarga, dimana pelakunya adalah ibu, bapak, kakek, kakak, dan paman. Disarankan agar seluruh calon pengantin mendapatkan pendidikan kesehatan tentang kebutuhan dasar tumbuh kembang anak serta peran dan fungsi keluarga dalam mewujudkan keluarga sejahtera.